DEVELOPMENT OF AN ARDUINO WIRELESS MONITORING DEVICE WITH RADIO MODULE OF LIQUID LEVEL (Multidisciplinary Journal of Science and Technology, 2024)
Today, measuring the levels of sliquids and flowing solids (cement, sand, alabaster, salt, soda, etc.) is of great importance in the automatic management of technological processes. Level sensors can be used for two purposes. In the first case, such sensors are called level detectors and give an alarm when the level reaches a certain point. The sensors of the second type are used for continuous control of the volume and quantity of the product in the container. It is also possible that most of the sensors of the second type have received the function of the sensors of the first type. That is, in addition to showing the level of the substance in the container, it can give a separate signal when it reaches a certain point. We used this method in this project.